Análise do transcriptoma de folhas de cana-de-açúcar submetidas à prolongada limitação hídrica usando RNA-Seq - Belesini, Aline Andrucioli [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In Brazil, the sugarcane culture has expanded to areas with prolonged drought seasons, which is constraining sugarcane production. In this study, the gene expression profiles of two sugarcane cultivars (Saccharum spp.), one tolerant and other sensitive to water stress, were assessed by the RNA-Seq technology. The de novo assembly of leaves transcriptome was held aiming to identify and to analyze differentially expressed genes between the cultivars involved with molecular response during water stress periods. In order to accomplish this, the two cultivars were planted in a greenhouse and 60 days after planting them, they were submitted to three potential controlled water soil (control, moderate drought and severe water deficit) and evaluated at 30, 60 and 90 days after treatments application. Using the RNA-Seq method were generated over a billion sequences, which allowed to obtain a total of 177,509 and 185,153 transcripts sequences for the tolerant and sensitive cultivars, respectively. The set of expressed transcripts were assembled using the Trinity program. These transcripts were aligned with Sorghum bicolor, Miscanthus giganteus, Arabidopsis thaliana sequences and sugarcane sequences available in public databases. This analysis allowed the identification of the set of sugarcane genes shared with other species, as well as led to the identification of novel transcripts not cataloged yet. The transcripts were annotated and categorized by the terms of the Gene Ontology (GO) into three categories: cellular component, molecular function and biological process for the two cultivars. The terms enzyme regulator and transcription regulator that lie within the molecular function category are highlighted within the terms associated with the differentially expressed genes between the contrasting cultivars, suggesting the importance of gene regulation for the studied cultivars. This study found different molecular patterns of the involved ...

No Brasil, a cultura da cana-de-açúcar tem se expandido para regiões com prolongados períodos de deficiência hídrica, o que vem limitando a produção sucroenergética. Neste estudo, os perfis de expressão gênica de duas cultivares de cana-de-açúcar (Saccharum spp.), uma tolerante e outra sensível ao estresse hídrico, foram avaliados através da tecnologia de RNA-Seq. A montagem de novo do transcriptoma de folhas foi realizada visando identificar e analisar os genes diferencialmente expressos entre as cultivares, envolvidos com a resposta molecular durante períodos de estresse hídrico. Para isso, as duas cultivares foram plantadas em casa de vegetação e aos 60 dias após o plantio foram submetidas a três controlados potenciais hídricos do solo (controle, déficit hídrico moderado e déficit hídrico severo) e avaliadas aos 30, 60 e 90 dias após a aplicação dos tratamentos. A partir do método RNA-Seq, foram geradas mais de um bilhão de sequências, as quais permitiram obter um total de 177.509 e 185.153 sequências de transcritos, para as cultivares tolerante e sensível, respectivamente. O conjunto de transcritos expressos foram montados com o auxílio do programa Trinity. Estes transcritos foram alinhados com sequências de Sorghum bicolor, Miscanthus giganteus, Arabidopsis thaliana bem como sequências de cana-de-açúcar disponíveis em bancos públicos. Esta análise permitiu identificar o conjunto de genes de cana-de-açúcar compartilhados com outras espécies, bem como levou à identificação de novos transcritos ainda não catalogados. Os transcritos foram anotados e categorizados através dos termos do Gene Ontology (GO) em três categorias: componente celular, função molecular e processos biológicos para as duas cultivares. Os termos regulador de enzima e regulador de transcrição que se encontram dentro da categoria função molecular estão em evidência dentro dos termos associados aos...
Keywords: Cana-de-açúcar; Expressão gênica; Plantas cultivares; Genes; Seqüenciamento de nucleotídeo; Genetica vegetal; Gene expression